Recurrent Painful Ophthalmoplegic Neuropathy: case series from a tertiary hospital and a systematic review - Assunção, Pablo Augusto Silva De; Murta, Nina Rosa Aparecida Felisardo; Moraes, Helena Providelli De; Silva, Marilia Fontenelle E; Gomez, Rodrigo Santiago (Headache Medicine, 2023)
Full abstract in PDF.